Navigating Through Uncertainty in the Era of COVID-19: Experiences of International Graduate Students in the United States - Sustarsic, Manca; Zhang, Jianhui (Journal of International Students, 2021)
With the spread of COVID-19 around the world, the lives of international students became affected by a sudden shift to online learning, sheltering in place, and travel restrictions. Drawing upon the stress and coping framework, this study explores the experiences and coping of international graduate students at a large Western research university in the United States. We employed a phenomenological inquiry of in-depth interviews with 20 participants. Findings reveal the increased levels of stress and anxiety among participants as they faced academic challenges, personal challenges, and immigration-related uncertainties. Over time, students developed emotion-focused and problem-focused coping strategies to minimize the impact of the pandemic on their lives. Participants’ concerns about the host country’s treatment of international students raise important questions about the future of international student mobility. Finally, this study demonstrates the need to develop emergency responding mechanisms of the host institution.